PENINGKATAN KAPASITAS UMKM DALAM PENYUSUNAN RENCANA BISNIS - aam amaningsih jumhur; Rahmat Darmawan (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2023)
AbstractMicro, Small and Medium Enterprises (MSMEs) in the Educational Tourism Village of Cisaat Subang Village are able to create jobs and add value, success in increasing MSMEs means strengthening business in the community, the existence of MSMEs in the Village is community participation in the economic activity sector. Village MSMEs in BUMDES coordination need more optimal development in an effort to maintain the continuity of their business. The UNJ Community Service team is holding capacity building with the theme of preparing business plans by inviting experienced practitioners. The aim of increasing the capacity of Cisaat Village MSME actors is to instill an understanding of the purpose of increasing the potential of MSMEs by building a positive mindset of Cisaat Village MSME actors in planning their business. The method for increasing the capacity of MSME actors in Cisaat Village is carried out with assistance (a) Preparing a business plan; (b) Create a cash flow to obtain funding from Financial Institutions. In conclusion, increasing capacity in preparing business plans with the participation of Cisaat Village MSMEs can generally be implemented well and smoothly. It is hoped that the results of increasing capacity in preparing business plans can be followed up by applying for capital loans from financial institutions to expand Cisaat Village MSME businesses.AbstrakUsaha Mikro Kecil Menengah (UMKM) di Desa Wisata Edukasi Desa Cisaat Subang mampu menciptakan  lapangan kerja dan nilai tambah, keberhasilan dalam meningkatkan UMKM berarti memperkokoh bisnis di masyarakat, keberadaan UMKM di Desa merupakan partisipasi masyarakat dalam sektor kegiatan perekonomian. UMKM Desa dalam koordinasi BUMDES perlu pembinaan lebih optimal dalam upaya mempertahankan keberlangsungan usahanya, team Pengabdian Pada Masyarakat UNJ menyelenggarakan peningkatan kapasitas dengan tema penyusunan rencana bisnis dengan mengundang para praktisi yang pengalaman. Tujuan peningkatan kapasitas pelaku UMKM Desa Cisaat adalah menanamkan pemahaman tujuan peningkatan potensi UMKM dengan membangun positive mindset pelaku UMKM Desa Cisaat dalam merencanakan usaha. Metode peningkatan kapasitas pelaku UMKM Desa Cisaat dilakukan dengan pendampingan (a) Penyusunan rencana bisnis; (b) Membuat chasflow untuk mendapatkan pendanaan dari Lembaga Keuangan. Kesimpulan, peningkatan kapasitas dalam penyusunan rencana bisnis dengan partisipasi pelaku UMKM Desa Cisaat yang secara umum dapat terlaksana dengan baik dan lancar. Diharapkan hasil peningkatan kapasitas dalam penyusunan rencana bisnis bisa ditindaklanjuti dengan mengajukan pinjaman modal kepada pihak lembaga keuangan untuk memperbesar usaha UMKM Desa Cisaat.